2019
DOI: 10.1007/s00059-019-4837-0
|View full text |Cite
|
Sign up to set email alerts
|

Alprostadil attenuates LPS-induced cardiomyocyte injury by inhibiting the Wnt5a/JNK/NF-κB pathway

Abstract: Background Clinical research has demonstrated that alprostadil has an anti-inflammatory effect; however, to date, its molecular mechanisms remain unclear. This study aimed to examine the anti-inflammatory activity and related mechanisms of alprostadil in lipopolysaccharide (LPS)-treated H9c2 cells. Methods Cell morphology was observed under an inverted light microscope, while cell viability was assessed with the 3‑(4,5-dimethylthiazolyl-2)-2,5-diphenyltetrazolium bromid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…Very recently, a study indicated that the activation of JNK promoted the activation of NF-κB, further increasing the release of inflammatory factors. 22 Moreover, the JNK inhibitor SP600125 inhibited PM2.5-induced expression of the inflammatory mediator IL-6 in human osteoarthritis synovial fibroblasts. 23 As predicted, in our study, we also found that GSK-3β inhibitors inhibited the ratio of p-JNK/JNK in HBECs caused by PM2.5.…”
Section: Discussionmentioning
confidence: 98%
“…Very recently, a study indicated that the activation of JNK promoted the activation of NF-κB, further increasing the release of inflammatory factors. 22 Moreover, the JNK inhibitor SP600125 inhibited PM2.5-induced expression of the inflammatory mediator IL-6 in human osteoarthritis synovial fibroblasts. 23 As predicted, in our study, we also found that GSK-3β inhibitors inhibited the ratio of p-JNK/JNK in HBECs caused by PM2.5.…”
Section: Discussionmentioning
confidence: 98%
“…ROR1 and FZD5 are receptors for Wnt5a, which have been shown to be upstream in the activation of NF-κB by Wnt5a ( Barbero et al, 2019 ; Chen et al, 2019 ; Tai et al, 2021 ). Moreover, LPS has been reported to activate the Wnt5a/JNK/NF-κB pathway in H9c2 cells ( Yu et al, 2020 ). Pretreatment with the JNK inhibitor SP60025 significantly reduced the levels of NF-κB in the nucleus which were higher than those induced by silenced Wnt5a (siWnt5a), indicating that other signaling pathways are involved in the Wnt5a/NF-κB pathway besides JNK ( Yu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that inhibition of the NF-κB signaling pathway downregulated the overexpression of Wnt5a induced by injury ( Sucre et al, 2020 ). In addition, LPS-induced activation of Wnt5a can indirectly regulate NF-κB expression through JNK signaling ( Yu et al, 2020 ). Zhao et al (2015) proposed that the upregulation of Wnt5a mediated a positive feedback loop in the inflammatory response through the PI3K/AKT/NF-κB signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Noncanonical Wnt5a signaling comprises two main pathways: Wnt5a/Ca 2+ pathway and the Wnt5a/JNK or planar cell polarity (PCP) pathway [37]. Therein JNK signaling was widely demonstrated to be involved in in ammation [36,38,39]. Activated JNK participated in stimulation of many in ammatory cytokines by LPS [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Therein JNK signaling was widely demonstrated to be involved in in ammation [36,38,39]. Activated JNK participated in stimulation of many in ammatory cytokines by LPS [39,40]. Phosphorylation of JNK mediated hepatoxicity in acetaminophen-induced ALF [20].…”
Section: Discussionmentioning
confidence: 99%